THE ROLE OF NATIONAL AND INTERNATIONAL SPORTS-SHOOTING, HUNTING AND COLLECTORS ORGANISATIONS IN TERMS OF THE FIREARMS CONTROL ACT 60 OF 2000 - Eugene van der Berg (Obiter, 2022)
The aim of this note is to examine the role of national and international sports-shooting, hunting and collectors organisations in the application of the Firearms Control Act 60 of 2000, as distinguished from the accredited organisations referred to in that Act.The Firearms Control Act finally came into operation on 1 July 2004 (Proc 28 in GG 26374 of 2004-05-28). The regulations made by the Minister of Safety and Security under section 145 of the Act came into operation on the same date (reg 114; GN R345 in GG 26156 of 2004-03-26).Some provisions of the Act and some regulations made under it, particularly those relating to accreditation (see par 3 2 below), had already come into operation on 1 July 2003 (R52 and R957 in GG 25153 of 2003-06-30).The Act repeals the whole of the Arms and Ammunition Act 75 of 1969 which previously regulated the possession of arms and ammunition. The new Act introduces an intricate scheme for the control of firearms quite unlike that provided for by the previous Act. The introduction of the new Act was accompanied by some controversy (and not a little drama). The Act attracted the attention of the High Court even before it came into operation. In South African Gun Owners Association v State President of the Republic of South Africa (TPD 2004-06-30 case number 16620/04) a seemingly ill-advised application by seven firearms-related organisations to interdict the new Act from coming into operation a few days before it was set to do so, was dismissed with attorney-and-client costs.The new Act and the regulations issued in terms thereof raise many new questions, some of them likely to remain unanswered for some time.